Malaysian Undergraduates’ Motivational Profiles : The Ideal L2 Learners and Motivated Learning Behaviour - Shanthi, Nadarajan (National University of Singapore, 2019)
Drawing on cluster analysis to define and describe L2 adult learners’ motivational profiles, this study uses an L2 motivational construct to analyse and interpret L2 learners’ identities in the language classroom. The study explored seven broad motivational and attitudinal dispositions for learning English. A 60-item survey was used to collect responses from 673 Malaysian undergraduates. Statistical calculations revealed 5 distinct motivational profiles and the ideal L2 learner self as the primary component effecting motivated learning behaviour. Only the highly extrinsic and the intrinsically motivated learner profiles obtained high positive mean scores for the target outcome. Subsequent learner profiles revealed both highly extrinsically and intrinsically motivated learner profiles which are indicative of learners willing to take additional English classes. The combined findings for externally regulated variables revealed that most students took the course to improve their grades, but the highly intrinsic profile group did not see grades and social groups as important. The combined findings for the internally regulated motives revealed that both extrinsically motivated groups, and amotivation profiles did not have a positive learning experience compared to the intrinsic profiles. While the Ideal L2 Self, and Ought To L2 Self were the controlling factors, positive positioning in terms of integrative and intrinsic orientation help learners move towards self-determinism, while negative positioning contribute to resistance, or non-participation within the group. Since different positionings impact how learners exercise agency, instructors may need to treat L2 learners’ first language and multicultural knowledge as valuable resources to promote greater self-confidence, positioning, and investment. L2 learners will continue to invest in the learning process, if they see English as bringing different forms of capital and access to resources. Language instructors must consider the different forms of capital that English language learners possess, and encourage learner participation to help learners construct positive identities, and value the learning process.